2020
DOI: 10.1080/09712119.2020.1828893
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fish oil, lycopene and organic selenium as feed additives on rabbit meat quality

Abstract: The aim of the study was to compare the quality of rabbit meat depending on the type of feed used. The animals were divided into 5 groups of 10 individuals and were fed ad libitum with feed for 55 days. The control group was fed with the addition of sunflower oil (4%), the feed of group FO was enriched with 4% odourless fish oil (FO), the feed of group FOLyc was enriched with 4% FO and 15 ppm lycopene (Lyc), the feed of group ROSe was enriched with 4% FO and selenized yeast (SeY) and the feed of group FOLycSe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Currently, reports about lycopene are gradually increasing. Previous research has shown that lycopene improved animal production performance ( 16 ), maintained intestinal health ( 17 ), ameliorated meat quality ( 18 ), ameliorated immunity ( 19 ) and regulated body metabolism ( 20 ), and has good application prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, reports about lycopene are gradually increasing. Previous research has shown that lycopene improved animal production performance ( 16 ), maintained intestinal health ( 17 ), ameliorated meat quality ( 18 ), ameliorated immunity ( 19 ) and regulated body metabolism ( 20 ), and has good application prospects.…”
Section: Introductionmentioning
confidence: 99%